The impact of partnered pharmacist medication charting in the emergency department on the use of potentially inappropriate medications in older people - Atey, Tesfay Mehari; Peterson, Gregory M.; Salahudeen, Mohammed S.; Wimmer, Barbara C. (Frontiers in Pharmacology, 2023)
A process redesign, partnered pharmacist medication charting (PPMC), was recently piloted in the emergency department (ED) of a tertiary hospital. The PPMC model was intended to improve medication safety and interdisciplinary collaboration by having pharmacists work closely with medical officers to review and chart medications for patients. This study, therefore, aimed to evaluate the impact of PPMC on potentially inappropriate medication (PIM) use. A pragmatic concurrent controlled study compared a PPMC group to both early best-possible medication history (BPMH) and usual care groups. In the PPMC group, pharmacists initially documented the BPMH and collaborated with medical officers to co-develop treatment plans and chart medications in ED. The early BPMH group included early BPMH documentation by pharmacists, followed by traditional medication charting by medical officers in ED. The usual care group followed the traditional charting approach by medical officers, without a pharmacist-collected BPMH or collaborative discussion in ED. Included were older people (≥ 65 years) presenting to the ED with at least one regular medication with subsequent admission to an acute medical unit. PIM outcomes (use of at least one PIM, PIMs per patient and PIMs per medication prescribed) were assessed at ED presentation, ED departure and hospital discharge using Beers criteria. Use of at least one PIM on ED departure was significantly lower for the PPMC group than for the comparison groups (2, p = 0.040). However, PIM outcomes at hospital discharge were not statistically different between groups. PIM outcomes on ED departure or hospital discharge did not differ from baseline within the comparison groups. In conclusion, PIM use on leaving ED, but not at hospital discharge, was reduced with PPMC. Close interprofessional collaboration, as in ED, needs to continue on the wards.